2021
DOI: 10.3389/fmed.2021.645550
|View full text |Cite
|
Sign up to set email alerts
|

Updated Evidence of the Association Between Elevated Serum Uric Acid Level and Psoriasis

Abstract: Background: Our earlier meta-analysis showed that the correlation between psoriasis and hyperuricemia might be region-dependent and that hyperuricemia was more common in patients with psoriasis in Western Europe. However, no further analysis could be conducted owing to the scarcity of data.Objective: Our study aimed to further explore the association between psoriasis and hyperuricemia.Methods: Six databases (PubMed, Embase, the Cochrane Central Register of Controlled Trials, the China National Knowledge Infra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 37 publications
2
14
1
Order By: Relevance
“…The SUA levels were considerably greater in patients with severe Pso who had a higher PASI score than those with mild and moderate Pso, with a significant positive association between SUA levels and PASI score ( p = 0.010). This was in line with the results of Zhang et al., 25 whereas Hernandez et al 26 . reported this relationship to be statistically not significant.…”
Section: Discussionsupporting
confidence: 92%
“…The SUA levels were considerably greater in patients with severe Pso who had a higher PASI score than those with mild and moderate Pso, with a significant positive association between SUA levels and PASI score ( p = 0.010). This was in line with the results of Zhang et al., 25 whereas Hernandez et al 26 . reported this relationship to be statistically not significant.…”
Section: Discussionsupporting
confidence: 92%
“…1 Erythematous scaly patches in different areas of the body are its primary features. Psoriasis affects 2-3% of the general population 2 and is associated with significant morbidity when present along with other comorbidities such as obesity, 3 cardiovascular disease, 4 hyperuricemia, 5,6 and chronic obstructive pulmonary disease. 7 In recent decades, increasing evidence has shown that metabolic syndrome (MetS) is a main complication of psoriasis.…”
Section: Introductionmentioning
confidence: 99%
“…However, the actual causal relationship between psoriasis and hyperuricemia remains unknown. As psoriasis and hyperuricemia are affected by a number of shared and separated genetic factors, a significantly higher level of uric acid was detected in psoriasis patients from the west but not from middle Asia and India in comparison with controls [35,36], indicating an ethnicity-specific correlation between psoriasis and hyperuricemia. In psoriasis, uric acid is considered as a byproduct of rapid skin cell turnover and systemic inflammation.…”
Section: Discussionmentioning
confidence: 90%